Biodescoloração dos corantes azul de metileno e cristal violeta por isolados Bacillus e Pseudomonas de origem ambiental - Batista, Nayara de Oliveira (2019)
Large amounts of toxic dyes from textile effluents are discarded in a natural water system, since some of the dyes are not absorbed in the process of dyeing of the tissues leading to changes mainly in aquatic flora and fauna, in addition to harmful effects to man. Several processes can be used to remove these dyes, however, the search for environmentally friendly and economical technologies is constant. Thus, the present work aimed at the biodescoloration and biodetoxification of methylene blue and violet crystal dyes, which are used in the textile industry. The bacterial isolates (A5 - Pseudomonas sp., Isolates A7, A8 and CA - Bacillus sp.) Were used, which are proven to produce laccase, which was calculated by the oxidation of ABTS (2,2' - azino - bis (3-ethylbenzothiazoline-6-sulfonic acid) dyes were tested at concentrations 50 and 100 mg L-1 for methylene blue and 0.0125 and 0.025 mg L-1 for crystal violet in BHI culture medium (Brain Heart Infusion Broth ), UV-VIS spectral bands, colony-forming units counting (CFU), ecotoxicity tests (cytotoxicity and phytotoxicity) and statistical analyzes were determined. All the isolates presented efficiency in degradation of The cytotoxicity tests using Escherichia coli revealed the loss of sensitivity to the dye, while in the phytotoxicity test there was no difference in the color of the dyes results of the solutions treated by the bacterial isolates compared to the untreated solutions. Statistical analysis indicated that the best isolates evaluated in the tests were those belonging to the genus Bacillus sp.